PENGARUH TERPAAN MEDIA SOSIAL INSTAGRAM @REKOSISTEM TERHADAP PEMENUHAN KEBUTUHAN INFORMASI MASYARAKAT MENGENAI PEMILAHAN SAMPAH DI INDONESIA - Tsaqila A'inurrohmah, (2024)
The unresolved waste problem in Indonesia can be overcome by providing the public with knowledge from the messages they consume, including about waste sorting. Rekosistem is a company in the waste management sector that uses Instagram as a medium for spreading messages about waste sorting. This research aims to examine the influence of social media exposure of @rekosistem Instagram account on providing audience's information needs regarding waste sorting using the Uses and Gratifications Theory. The research was conducted using a quantitative descriptive approach. Data collection was carried out online using a survey method with a closed questionnaire to 100 respondents taken from followers of the @rekosistem Instagram account. The sampling technique was carried out using simple random sampling. The results of the research show that there is a strong and positive relationship between social media exposure of @rekosistem Instagram account and followers' information fulfilment regarding waste sorting. Therefore, it can be concluded that social media exposure of @rekosistem Instagram account has a significant effect on fulfilling the audience's information needs relating to waste sorting in Indonesia.